Transmembrane ROOM proteins ensure rooms for germ cells by maintaining intercellular bridges - Kenta Sugiura; Ichiro Kawasaki; Hidetaka Kosako; Ken Sato (Proceedings of the National Academy of Sciences, 2026)
Germ cells of diverse species form a syncytium, which is a multinucleated cell complex, and share cytoplasmic components via intercellular bridges. Here, we demonstrate that the paralogous transmembrane proteins ROOM-1 and ROOM-2, identified through the proteomic analysis of maternal membrane proteins, are essential for the maintenance of germ cell compartments from the rachis of Caenorhabditis elegans gonads. Although animals lacking each protein are fertile, the loss of both proteins resulted in complete sterility due to compartmentalization failure of individual germ cells in the late larval and adult gonads. Additionally, the ROOM proteins colocalize specifically to the intercellular bridge with F-actin and ANI-2, a protein organizing the intercellular bridge of germ cells. The localizations of ANI-2 and ROOM-1/2 on the rachis bridge were interdependent. Thus, the transmembrane ROOM proteins redundantly function to ensure “rooms” for germ cells by maintaining the intercellular bridges.